2020
DOI: 10.1172/jci.insight.136279
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cell-free DNA predicts pediatric cerebral malaria severity

Abstract: Role of funding:The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 62 publications
2
13
0
Order By: Relevance
“…However, in this study, samples were collected after death. Finally, a recent study reported higher levels of IL-8 in retinopathy-positive CM children who died than in survivors and UM children, similar to our results [ 51 ]. The authors claim that retinopathy diagnosis improves clinical CM specificity, as it is related to iRBC sequestration in brain.…”
Section: Discussionsupporting
confidence: 92%
“…However, in this study, samples were collected after death. Finally, a recent study reported higher levels of IL-8 in retinopathy-positive CM children who died than in survivors and UM children, similar to our results [ 51 ]. The authors claim that retinopathy diagnosis improves clinical CM specificity, as it is related to iRBC sequestration in brain.…”
Section: Discussionsupporting
confidence: 92%
“…However, in this study, samples were collected after death. Finally, a recent study reported higher levels of IL-8 in retinopathy-positive CM children who died than in survivors and UM children, similar to our results [51]. The authors claim that retinopathy diagnosis improves clinical CM speci city, as it is related to iRBC sequestration in brain.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, platelet counts are inversely correlated with extracellular histone levels in the Malawi cohort, and extracellular histones promote both procoagulant and barrier-disruptive pathways ( 22 ). Additionally, activated neutrophils, a source of extracellular histones, are linked to CM severity in the Malawi cohort ( 73 , 74 ). The phenotypes and effector functions of platelets are modified by microvesicles and extracellular histones released by injured cells ( 75 , 76 ) and neutrophils ( 77 ).…”
Section: Discussionmentioning
confidence: 99%